2022
DOI: 10.1002/wsbm.1549
|View full text |Cite
|
Sign up to set email alerts
|

New developments in the biology of fibroblast growth factors

Abstract: The fibroblast growth factor (FGF) family is composed of 18 secreted signaling proteins consisting of canonical FGFs and endocrine FGFs that activate four receptor tyrosine kinases (FGFRs 1-4) and four intracellular proteins (intracellular FGFs or iFGFs) that primarily function to regulate the activity of voltagegated sodium channels and other molecules. The canonical FGFs, endocrine FGFs, and iFGFs have been reviewed extensively by us and others. In this review, we briefly summarize past reviews and then focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 1,566 publications
(2,214 reference statements)
1
74
0
Order By: Relevance
“…An FGF can bind to multiple FGFRs. FGFs rely on heparan sulfate proteoglycan (HSPG) and Klotho-type coreceptors to improve their binding to FGFRs (Ornitz and Itoh, 2022). After FGF-FGFR binding, through the autophosphorylation of FGFRs, with the help of FGFR substrate 2 and PLCγ, signals are transferred to the RAS-ERK, PI3K/AKT, PKC, and JAK-STAT signaling cascades, which mediate the survival, proliferation, differentiation, or migration of cells (Inomata et al, 2015;Katoh, 2018).…”
Section: Fibroblast Growth Factormentioning
confidence: 99%
“…An FGF can bind to multiple FGFRs. FGFs rely on heparan sulfate proteoglycan (HSPG) and Klotho-type coreceptors to improve their binding to FGFRs (Ornitz and Itoh, 2022). After FGF-FGFR binding, through the autophosphorylation of FGFRs, with the help of FGFR substrate 2 and PLCγ, signals are transferred to the RAS-ERK, PI3K/AKT, PKC, and JAK-STAT signaling cascades, which mediate the survival, proliferation, differentiation, or migration of cells (Inomata et al, 2015;Katoh, 2018).…”
Section: Fibroblast Growth Factormentioning
confidence: 99%
“…Multiple secreted proteins in the lung, including cytokines and growth factors, can regulate virus infection, the inflammatory response, and post-infection repair to combat severe IAV disease. Fibroblast growth factors (FGFs) are a family of secreted proteins that regulate tissue maintenance, metabolism, regeneration, and repair of adult tissues by binding to the extracellular domain of four transmembrane tyrosine kinase FGF receptors (FGFRs) [ 5 , 6 ]. In the developing lung, FGF1, FGF2, FGF3, FGF7, FGF9, FGF10, and FGF18 all perform essential regulatory functions mediating organogenesis [ 7 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with these pieces of evidence, Kuslak and colleagues [26] have demonstrated that the spontaneous mouse SV shape (svs) mutation, which affects budding/branching of the SV is caused by a mutation of the Fgfr2 gene that perturbs splicing of the gene. Authors also show that the alternative splice isoform Fgfr2c, whose cognate ligands are FGF7 and FGF10 [28], is the main isoform expressed in the SV [26]. Previous work has shown that both FGF7 (also known as KGF) and FGF10 are expressed in the mesenchyme surrounding SVs during development and, as mentioned earlier, that both factors can promote SV branching in vitro [18,19].…”
Section: Discussionmentioning
confidence: 70%